Use of cyanoacrylate glue for the sutureless securement of epicutaneo-caval catheters in neonates. Issue 5 (September 2022) - D'Andrea, Vito; Pezza, Lucilla; Barone, Giovanni; Prontera, Giorgia; Pittiruti, Mauro; Vento, Giovanni
Introduction: Epicutaneo-caval catheters (ECC) are pivotal for drug and fluid infusion in neonates. Given the intrinsic importance of the catheter for the patients' health and the need to avoid stressful and painful procedures on premature or critically ill newborns with fragile and poor vein asset, it is clearly necessary an accurate bundle for ECC insertion and management to avoid complications that may lead to non-elective ECC removal. Among others, dislodgment is an acknowledged complication, and conventionally adopted fixing devices seem alone unsatisfying in relation to ECC securement. Object: To evaluate the usefulness of medical Cyanoacrylate Glue (CG) as a solution to strengthen conventional ECC securement. Methods: Since the use of CG has become part of our ECC insertion bundle in 2018, the present study compares all term and preterm neonates admitted in our NICU in 2018 who required an ECC for any cause (92 cases) with an historical cohort formed by all neonates who required an ECC in 2017 (80 patients). Results: CG added to usual securement devices is effective in reducing ECC accidental dislodgment. Moreover, it is easy and safe to apply and remove, limits bleeding and oozing at the puncture site, and may also be an effective antimicrobial mechanical barrier.